ANALYSING THE EFFECT OF LEARNING BY SIMULATION ON THE SPEED AND ACCURACY DECISION MAKING OF VOLLEYBALL PLAYERS - Merzoug, Djamel; BELKADI, Adel; sebbane, Mohamed; Abed, Fouad; Abdedaim, adda (http://journal-science.org/en/article/829.html, 2017)
The purpose of this study was to verify the efficiency of learning by simulation intervention programme on the speed and accuracy on decision making of Basic Volleyball Skills (Serving, Sitting and Dig & Blocked) of 24 volleyball players. Material. Two intact groups of volleyball academy players participated in this study. One academy group participated in the perceptual learning simulation, which included activities, game analysis, tactical volleyball discussions, volleyball rule discussions and decision making, they were spatially and temporally occluded to provide varying amounts of information to the participant. The other academy group served as the control group and completed both the pre- and post-tests bay using "Super Lab (V 4.04) test. Our study was designed and implemented to address three aspects of decision making in Volleyball. First, speed and accuracy of decision making was assessed. In this research, Super Lab (V 4.04) test 3D basic Situation skills from Volleyball situation matches of 15 3D basic Situation skills -Multiple Object Tracking(Romeas et al., 2016; Takahashi, Ikeya, Kano, Ookubo, & Mishina, 2016) was used to identify any changes after a learning simulation programme. The participants scores on each of these variables were processed to determine if there were any significant differences from pre- to post-test performance, and if there were any significant differences between the subjects who received the perceptual learning by simulation and the subjects in the Control group. Methods. All data collected from all the different tests were entered in an Excel format and processed using the SPSS statistics programme and the appropriate t-tests for repeated measures, were completed to determine group differences (Table 2). The significance level for all test variables was an alpha level of 0.05. The following procedures were followed in the development and implementation of this research. The researcher decided that a computer-based test using "Super Lab (V 4.04) test 3D basic Situation skills from Volleyball situation matches would provide the necessary challenge to players’ decision making and also allow a measurement of the speed and accuracy with which they made their decisions. Two different kinds of data were analyzed: Speed and Accuracy of Decision Making, As the first situation is presented on the computer screen, a timer is activated. Players will see the action up to the point where the action is “frozen”. Watch and when the screen freezes players can immediately make their decision by clicking with on the keyboard eight second were done to answer quickly time and accuracy of your decision will be measured.Results. Results showed important improvement in the decision making by participants in both the experimental and the control groups. Both groups also indicated a significant deterioration in the accuracy of their decisions. The similarity in the post-test scores of the two groups led to the conclusion that learning simulation has affected the decision-making for the experimental group. Our results suggest different sources of visual information work collectively to facilitate player’s anticipation in time-constrained sports and reinforce the complexity of player’s perception. Another Suggestion is made for the design of future technique to improve decision making. The results showed a significant improvement in speed of decision making for both the experimental Group 1 and the Control group 2 (Table 3). It can also be noticed that the variability scores within each group, as indicated by the standard deviation, was less on the post-tests. The SD on the pre-test for the experimental group was 2.95s, which dropped to .90s on the post-test. The SD on the pre-test for the Control group was 1.72s on the pre-test and only .83s on the post-test. This means that both groups not only became faster, but also that the subjects within each of the groups were more similar to each other in the speed of their decision making on the post-test.Between group differences showed that the subjects were not significantly different from each other, either on the pre-test or on the post-test (Table 6). The mean score for accuracy was slightly higher on the pre-test for Group 1 (experimental), but the mean score for both groups on the post-test was almost identical (2.95 correct and 2.86).Conclusion. We can conclude that our designed learning by simulation programme develop mutually the speed and accuracy of players’ decision making which can rely on (3D) basic Situation skills and video match playing feedback, to raise declarative and technical skills Basic Volleyball Skills (Serving, Sitting and Dig & Blocked).
Keywords: Learning, Simulation, Decision-Making, volley ball.